PENENTUAN LOKASI MINIMARKET DI KECAMATAN CIBIUK DENGAN MENGGUNAKAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) - Widy Yudha Rahmat Wiyata; Andri Ikhwana (Institut Teknologi Garut, 2016)
The economic development and social style, have infact necesery level physikolog to saved buyer, and good service ,and quality products need, and then the modern market as necessaries where service does with him self by customer because the market not avallable a service (pramuniaga) , wich special consumer service ,the modern market is movement up in Indonesia is mini market. The same condition in distric not except in Garut Regency , wich the people always do buy is super market and mini market , because is easy to choose the goods is need, and save to buy . The aim of riset is to know for minimarket location fixed which based criteria abd alternatif at Cibiuk Regency in Garut. In location minimarket establish with Analytical Herarkhi Proses (AHP) metod. AHP is ones of model establish suport wich development by Thomas Saary (1993). The resul of riset is that the Analytical herarkhi process (AHP), can do for identification to establesh minimarket location at Cibiuk distric in Garut , with to see the location minimarket which to the research.